PEMBERDAYAAN LANSIA KUNCI PERILAKU HIDUP SEHAT DI USIA SENJA - Sunandar, Kuslan; Ardiwinata, Jajat S; Suryadi, Ace; Shantini, Yanti (JURNAL RISET KESEHATAN POLTEKKES DEPKES BANDUNG, Online ISSN 2579-8103, 2025)
Empowerment of the elderly can be carried out in various aspects, one of which is health education. The welfare of the elderly is expected to increase through empowerment activities. The government together with the community and families must cooperate in improving social welfare for the elderly so that the physical, mental, and socioeconomic conditions of the elderly can function reasonably because these conditions are related to the diseases they suffer. More than fifty percent of elderly who live with their families or who live in nursing homes suffer from non-communicable diseases (NCDs). NCDs are the leading cause of death in the world with contribution of 62%. Currently, non-communicable diseases are on the rise as a result of an unhealthy lifestyle. The study aimed to determine the empowerment of elderly in carrying out healthy living behaviors. The research method used survey research. Quantitative data analysis was carried out using percentages. Data collection used an instrument in the form of a questionnaire on healthy living behavior in the elderly. Data was collected by interviews with 18 elderly people. Samples were selected using purposive sampling technique. Most of the elderly have unhealthy lifestyle behaviors, with percentage of more than 50% on various aspects such as water consumption, physical activity, diet, mental stimulation, sleep quality, as well as eating and drinking habits, lack of adherence to medication and health checks. This can negatively impact their overall health. Recommendations must be pursued for development of a problem-solving-based elderly empowerment model in improving healthy living behaviors